(untitled) (European Journal of Marketing and Economics, 2022)
Transition of Georgia to market economy is a complex and continuous process, closely related to both, economic growth and social challenges. In this regard domestic as well as foreign direct investments are one of the mechanisms of utmost importance. The country with economy in transition has many social-economic problems that make it essential for government to look for the most efficient ways of solving them implementing proper investment strategy.The paper considers the main trends and tendencies of investments from macroeconomic point of view, concerning the governmental investment policy aspects, investment climate, the dynamics of investments flows, capital revenues, investments share in GDP, the structure of investments in term of countries, sectors, etc. The article considers the core issues of the investment policy in Georgia from pragmatic as well as conceptual point of view, where the role and importance of investment policy are presented, legislative base of investments are discussed, inevitability of transparency, measurability and effectiveness of investment process is reasoned, proactive investment approach is prioritized, the importance of privatization policy is given, forms of privatization and their effectiveness are analyzed, complex utilization of investment marketing instruments, effective management of investment cycle, facilitation of post-investment activity, investigation of investment potential, Brown-field and Green-field investments and the PPI model and other topical questions are also characterized. Herewith, the author suggests some corresponding problem-solving recommendations which, as the author suggests, will help policy implementation persons at state, regional and local governmental levels of the country.